2005
DOI: 10.1016/j.molcel.2005.07.021
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding Selectivity of MeCP2 Due to a Requirement for A/T Sequences Adjacent to Methyl-CpG

Abstract: DNA methylation is interpreted by a family of methyl-CpG binding domain (MBD) proteins that repress transcription through recruitment of corepressors that modify chromatin. To compare in vivo binding of MeCP2 and MBD2, we analyzed immunoprecipitated chromatin from primary human cells. Genomic sites occupied by the two MBD proteins were mutually exclusive. As MeCP2 was unable to colonize sites vacated by depletion of MBD2, we tested the hypothesis that methyl-CpG alone is insufficient to direct MeCP2 binding. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
295
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(312 citation statements)
references
References 65 publications
15
295
1
1
Order By: Relevance
“…By analyzing Kaiso-binding sites in HEK293T cells, Ruzov et al found that Kaiso associates with methylated CpGs but not CTGCNA sites, and importantly, their data show that only the methylated DNA-binding function of Kaiso is required in early Xenopus laevis development [37]. It should be noted that binding of MBPs to methylated DNA appears to be sequence-specific: additional DNA sequence surrounding the CpG site(s) is important [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing Kaiso-binding sites in HEK293T cells, Ruzov et al found that Kaiso associates with methylated CpGs but not CTGCNA sites, and importantly, their data show that only the methylated DNA-binding function of Kaiso is required in early Xenopus laevis development [37]. It should be noted that binding of MBPs to methylated DNA appears to be sequence-specific: additional DNA sequence surrounding the CpG site(s) is important [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…This family of proteins consists of five well-characterised members (MeCP2, MBD1, MBD2, MBD3 and MBD4) (Esteller, 2005a). MBD proteins are associated with hypermethylated CpG island promoters of tumour-suppressor genes and their transcriptional silencing (Esteller, 2005a), showing remarkable specificity in vitro and in vivo Klose et al, 2005).…”
Section: Estellermentioning
confidence: 99%
“…No apparent difference in MECP2 binding activity to CpG 3 was observed between methylated and unmethylated states. It has been reported that an [A/T] ≄4 , a sequence adjacent to methyl‐CpG, is necessary for high‐affinity MECP2 binding 12. Four A/T bases were observed within the 3 bases of CpG1 and within 4 bases of CpG3, whereas CpG2 contained no A/T run.…”
Section: Resultsmentioning
confidence: 99%